2011
DOI: 10.1029/2010jc006895
|View full text |Cite
|
Sign up to set email alerts
|

Eddy properties in the California Current System

Abstract: [1] Eddy detection and tracking algorithms are applied to both satellite altimetry and a high-resolution (dx = 5 km) climatological model solution of the U.S. West Coast to study the properties of surface and undercurrent eddies in the California Current System. Eddy properties show remarkable similarity in space and time, and even somewhat in polarity. Summer and fall are the most active seasons for undercurrent eddy generation, while there is less seasonal variation at surface. Most of the eddies have radii … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
202
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(233 citation statements)
references
References 52 publications
29
202
1
1
Order By: Relevance
“…They 5 can be applied to altimetry data sets or with realistic high-resolution numerical model outputs, which also offer the opportunity to study both surface and subsurface eddies, as well as three-dimensional structures. Several comparisons have been done with both data sets and literature Kurian et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They 5 can be applied to altimetry data sets or with realistic high-resolution numerical model outputs, which also offer the opportunity to study both surface and subsurface eddies, as well as three-dimensional structures. Several comparisons have been done with both data sets and literature Kurian et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the calculation of the second derivative of SLA fields amplifies the error Kurian et al, 2011). The application of the Hanning filter notably reduces the noise, but at the same time weakens the signal of some structures, making 15 them difficult to be detected by the algorithm.…”
mentioning
confidence: 99%
“…Several automated eddy detection schemes are found in the literature (Jeong and Hussian 1995;Portela 1997;Sadarjoen et al 1998;Sadarjoen and Post 2000;Isern-Fontanet, García-Ladona, and Font 2006;Chaigneau, Gizolme, and Grados 2008;Nencioli et al 2010;Chelton et al 2007;Chelton, Schlax, and Samelson 2011;Kurian et al 2011;Faghmous et al 2015). However, studies have shown that when these algorithms are applied over the same data set, they provide significant statistical differences (Nencioli et al 2010;Souza, Montegut, and Traon 2011).…”
Section: Eddy Detection Methodsmentioning
confidence: 99%
“…Now, the idea of combining different methods, both dynamical and geometrical, seems to be more satisfying. Kurian et al (2011) illustrated the complementarity between the Okubo-Weiss criteria and geometrical methods using each method successively depending on their need. In the present study we also combine these two properties, but differently from Kurian et al (2011), our scheme uses both properties simultaneously to define an eddy (Halo 2012), and minimizes considerably the presence of threshold values, hence minimizing subjectivity.…”
Section: Eddy Detection Methodsmentioning
confidence: 99%
“…Different mechanisms for the generation of eddies in eastern boundary upwelling regions have been proposed (e.g., Liang et al, 2012). Barotropic and baroclinic instabilities of the near-coastal currents (Pantoja et al, 2012) triggered by, e.g., the passage of poleward propagating coastal trapped waves (Zamudio et al, 2001(Zamudio et al, , 2007, wind perturbations (Pares-Sierra et al, 1993), or interactions of the large-scale circulation with the bottom topography (Kurian et al, 2011) are the main processes identified for the eddy generation in eastern boundary upwelling regions. In the TANWA, the period of maximum eddy generation (June/July) is characterized by a strong near-surface boundary current, the MC (Lázaro et al, 2005) suggesting dynamic instabilities of the boundary current as an important generation mechanism.…”
Section: Seasonal Variability Of Eddy Generationmentioning
confidence: 99%